IMPACT OF CASH FLOW COMPONENTS, NET INCOME AND COMPANY SIZE ON STOCK RETURN - Magda Ella Wiranti; Moh. Hudi Setyo Bakti; Sochib Sochib (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
This study aims to obtain empirical evidence of the effect of: Components of Cash Flow, Net Profit, and Firm Size on the level of Stock Return. This research is a quantitative research. The type of data in this study is secondary data. The data source used is data retrieval from the annual financial statements of consumer goods industry companies on the Indonesia Stock Exchange (IDX). The population in this study is the Consumer Goods Industry listed on the Indonesia Stock Exchange (IDX) in 2016-2019. Researchers determine the number of company samples taken by purposive sampling technique. The analytical method used is multiple regression analysis. The results showed that the cash flow component had no significant effect on stock returns, net income had a significant effect on stock returns and firm size had no significant effect on stock returns.